Pengaruh Sales Growth, Capital Intensity, Earnings Management Terhadap Tax Avoidance: Moderasi Company Size - Saputri, Diva Septia; Rizkyana, Fitrarena Widhi (Universitas Sains dan Teknologi Komputer, 2025)
Tax avoidance can be detrimental to the country because it reduces the state's revenue. This study aims to analyze the effect of sales growth, capital intensity, and earnings management on tax avoidance with company size as a moderating variable. The population of this study comprises 221 manufacturing companies listed on the IDX in 2020-2024, with a sample of 64 companies selected via purposive sampling based on specific criteria, yielding a total of 320 observations analyzed using panel data regression (E-Views 12). The results show that sales growth directly affects tax avoidance, and company size moderates the relationship between sales growth and tax avoidance. However, capital intensity and earnings management do not have a significant effect, and company size cannot moderate the relationship between capital intensity and earnings management with tax avoidance. These findings emphasize that high sales growth can encourage companies to comply with tax regulations, thereby reducing tax avoidance, and that this effect can be suppressed by large company size due to greater reputational pressure and scrutiny. This study expands on previous research by making company size a moderating variable in the relationship between sales growth, capital intensity, and earnings management and tax avoidance.